New physical and mathematical diagnosis of fetal monitoring: clinical application prediction (2012)
Despite being a daily used exam in the obstetric clinic, the criteria for the analysis of fetal heart monitoring are not unanimous and its diagnosis presents problems as subjectivity and not reproducibility. The objective of this work is to develop a physical and mathematical diagnostic methodology of the fetal cardiac dynamics that overcomes the objectivity and reproducibility difficulties of the traditional diagnosis. This is a diagnostic concordance study, based on the application of entropy law, that doesn't require statistical analysis. Values of probability and S/k relation of the entropy law were calculated for the cardiac frequencies presented in discreet time intervals, in three prototypes and 12 normal and pathological fetal monitoring tracings, developing a theoretical prediction based on the probability value, and the S/k relation. Normality, disease and the evolution between them were differentiated. The S/k proportion for normal fetal monitoring oscillates between 1.7044 and 2.1576. According to the prediction, 40% of the conventional clinical diagnoses can be improved with these calculations. A new methodology of predictive clinical application and preventive character was built with physical and mathematical laws.